EVIDENCE OF STUDENT PERFORMANCE - Abdurakhmonov Mehroj; Lola Xayrulloyeva Dilshod qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article discusses the evidence of student performance and the importance of assessing it. Various assessment methods play an important role in determining the knowledge, skills and competencies of students in the educational process. The article discusses the main evidence determining student performance, its types and modern assessment approaches. It also considers the possibilities of improving the quality of education and improving the teaching process through this evidence.